A comparison of the assessment of mitral valve area by continuous wave Doppler and by cross sectional echocardiography. Issue 4 (April 1987) - Loperfido, F; Laurenzi, F; Gimigliano, F; Pennestri, F; Biasucci, L M; Vigna, C; De Santis, F; Favuzzi, A; Rossi, E; Manzoli, U
Abstract : Transmitral pressure half time (PHT) was assessed by continuous wave Doppler in 44 patients with rheumatic mitral valve stenosis (14, pure mitral valve stenosis; 15, combined mitral stenosis and regurgitation; and 15 with associated aortic valve regurgitation). The mitral valve area, derived from transmitral pressure half time by the formula 220/pressure half time, was compared with that estimated by cross sectional echocardiography. The transmitral pressure half time correlated well with the mitral valve area estimated by cross sectional echocardiography. The correlation between pressure half time and the cross sectional echocardiographic mitral valve area was also good for patients with pure mitral stenosis and for those with associated mitral or aortic regurgitation. The regression coefficients in the three groups of patients were significantly different. Nevertheless, a transmitral pressure half time of 175 ms correctly identified 20 of 21 patients with cross sectional echocardiographic mitral valve areas less than 1.5 cm2. There were no false positives. The Doppler formula significantly underestimated the mitral valve area determined by cross sectional echocardiography by 28(9)% in 19 patients with an echocardiographic area greater than 2 cm2 and by 14.8 (8)% in 25 patients with area of less than 2 cm2. In thirteen patients with pure mitral valve stenosis Gorlin's formula was used to calculate the mitral valve area. This was overestimated by cross sectional echocardiography by 0.16 (0.19) cm2 and underestimated by Doppler by 0.13 (0.12) cm2. Continuous wave Doppler underestimated the echocardiographic mitral valve area in patients with mild mitral stenosis. The Doppler formula mitral valve area = 220/pressure half time was more accurate in predicting functional (haemodynamic) than anatomical (echocardiographic) mitral valve area.